Implementation and evaluation of the Multi-connection Tactile Internet Protocol and API - Rico, Delia; Grinnemo, Karl-Johan; Brunstrom, Anna; Merino-Gómez, Pedro (My University, 2022)
Tactile Internet defines applications for remotely controlling and manipulating critical devices that require perceived real-time operation with additional demanding requirements like reliability. These use cases with stringent requirements demand adequate transport protocols to take advantage of the underlying possibilities. Traditional transport-layer solutions like TCP and UDP are no longer sufficient, hence novel protocols are being developed to support these applications. In this paper, we present an implementation and evaluation of the Multi-connection Tactile Internet Protocol (MTIP), a transport layer proposal to support these communications. MTIP uses application and network status information to perform an intelligent selection of paths in order to improve reliability and latency. In our evaluations, we study how the different configurations of the MTIP algorithm affect this selection and we see a direct trade-off where, with more restrictive thresholds, MTIP can increase the packets received correctly at the cost of sending extra duplicate packets.
Keywords: Protocolos de comunicaciones; Multi-connectivity; Transport protocols; Context Awareness; Tactile Internet; API